MOBILITAS PEKERJA PADA KAWASAN INDUSTRI PIYUNGAN DI KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - , MOHAMMAD ISNAINI SADALI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Industrial development will affect on the development of the region and also peoples mobility in the region. Piyungan Industrial Estate growth causes high rise of worker needs which is means more employment for local people and also people mobility from other area. Worker mobility process in Piyungan Industrial Estate is not only guided by economic factors, but also the regional policy at Bantul District. People mobility trend is generally heading to urban area as a growth centre, but there is an unique phenomenon that is need to be studied. People mobility shifts toward suburban or new growth pole outsite the Yogyakarta City. This research aims are: (1) assess the relationship between Piyungan Industrial Estate and worker mobility